Key Bioturbator Species Within Benthic Communities Determine Sediment Resuspension Thresholds - de Smit, Jaco C.; Brückner, Muriel Z. M.; Mesdag, Katherine I.; Kleinhans, Maarten G.; Bouma, Tjeerd J. (Frontiers in Marine Science, 2021)
Abundant research has shown that macrobenthic species are able to increase sediment erodibility through bioturbation. So far, however, this has been at the level of individual species. Consequently, we lack understanding on how such species effects act on the level of bioturbator communities. We assessed the isolated and combined effects of three behaviorally contrasting macrobenthic species, i.e., Corophium volutator, Hediste diversicolor, and Limecola balthica, at varying densities on the critical bed shear stress for sediment resuspension (τcr). Overall, the effect of a single species on sediment erodibility could be described by a power function, indicating a relatively large effect of small bioturbator densities which diminishes toward higher individual density. In contrast to previous studies, our results could not be generalized between species using total metabolic rate, indicating that metabolic rate may be only suitable to integrate bioturbation effects within and between closely related species; highly contrasting species require consideration of species-specific bioturbation strategies. Experiments at the benthic community level revealed that the ability of a benthic community to reduce τcr is mainly determined by the species that has the largest individual effect in reducing τcr, as opposed to the species that is dominant in terms of metabolic rate. Hence, to predict and accurately model the net effect of bioturbator communities on the evolution of tidal flats and estuaries, identification of the key bioturbating species with largest effects on τcr and their spatial distribution is imperative. Metabolic laws may be used to describe their actual activity.